The Crystallization of Amorphous Calcium Carbonate is Kinetically Governed by Ion Impurities and Water. Issue 5 (14th February 2018) - Albéric, Marie; Bertinetti, Luca; Zou, Zhaoyong; Fratzl, Peter; Habraken, Wouter; Politi, Yael
Abstract: Many organisms use amorphous calcium carbonate (ACC) and control its stability by various additives and water; however, the underlying mechanisms are yet unclear. Here, the effect of water and inorganic additives commonly found in biology on the dynamics of the structure of ACC during crystallization and on the energetics of this process is studied. Total X‐ray scattering and pair distribution function analysis show that the short‐ and medium‐range order of all studied ACC samples are similar; however, the use of in situ methodologies allow the observation of small structural modifications that are otherwise easily overlooked. Isothermal calorimetric coupled with microgravimetric measurements show that the presence of Mg 2+ and of PO4 3− in ACC retards the crystallization whereas increased water content accelerates the transformation. The enthalpy of ACC with respect to calcite appears, however, independent of the additive concentration but decreases with water content. Surprisingly, the enthalpic contribution of water is compensated for by an equal and opposite entropic term leading to a net independence of ACC thermodynamic stability on its hydration level. Together, these results point toward a kinetic stabilization effect of inorganic additives and water, and may contribute to the understanding of the biological control of mineral stability. Abstract : Amorphous calcium carbonate (ACC) is a versatile biomineral tuned by additives and water to form long lasting phases or transient precursors. However, the mechanisms of this stabilization are yet unknown. The effects of additives on the structure dynamics during crystallization and the energetic landscape of ACC are studied. It is shown that kinetics governs the transformation.